Carbon capture and storage from the boiler to the fleet - A canadian case study - Douglas, Peter L.; Croiset, Eric; Elkame, Ali; Alie, Colin; Shafeen, Ahmed; Hashim, Haslenda (2006)
This paper presents a techno-economic analysis of the capture and storage of CO2 from a single coal fired boiler with extensions to a fleet of coal, natural gas, nuclear, hydroelectric and wind generating stations. AspenPlus™ was used to simulate a 500 MW coal boiler c/w steam cycle and MEA absorption process. The energy required by the absorption process resulted in a ~30% de-rate in the generating station output. 14,000 tonnes/day of pure CO2 captured and compressed from the boiler was transported and injected into a saline aquifer approximately 125 km from the generating station and at least 800 m beneath the earth’s surface under supercritical conditions, (31.1°C, 7.38 MPa). The cost to transfer CO2 from the boiler and inject it underground is ~10 US$/tonne of CO2. The extension from a single boiler to the entire fleet of generating stations was formulated as an MILP and implemented in GAMS. A 3% fleet-wide reduction in CO2 emissions was achieved by fuel-balancing alone. Deeper reductions, however, required a combination of CO2 capture and storage, fuelswitching and new capacity including IGCC, NGCC and nuclear. For example, the cost of electricity increased by ~59% when reducing the fleet-wide emissions by 60%.